PENGARUH PEMANFAATAN SOSIAL MEDIA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA MANAJEMEN PERKANTORAN DAN LAYANAN BISNIS KELAS X DI SMK NEGERI 1 BITUNG - ., Seinca; Kambey, Joseph P.; Winokan, Amsje (Jurusan Pendidikan Ekonomi Fakultas Ekonomi dan Bisnis UNIMA, 2025)
This study aims to determine the effect of social media utilization and learning motivation on the learning outcomes of office management and business service class X students at SMK Negeri 1 Bitung. This study uses a quantitative approach and uses primary data through distributing questionnaires to 75 office management and business service class X students at SMK Negeri 1 Bitung. The results of the study obtained a multiple linear regression equation Ŷ = 5.011 + 0.546 X₁ + 0.405X₂. learning motivation has a significant effect on learning outcomes with a t-count value> t-table, namely (6.800> 1.993). Then the results of the F test prove that the use of social media and learning motivation simultaneously have a significant effect on the learning outcomes of office management and business service class X students at SMK Negeri 1 Bitung with an F-count value greater than the F-table, namely (557.18> 3.12) with a significance value of 0.000 <0.05. The conclusion is that the use of social media and learning motivation have a significant effect both partially and simultaneously on the learning outcomes of office management and business services students of class X at SMK Negeri 1 Bitung. Keywords: Use of Social Media, Learning Motivation, Learning Outcomes